Human impacts on sediment in the Yangtze River: A review and new perspectives - Yang, H.F.; Yang, S.L.; Xu, K.H.; Milliman, J.D.; Wang, H.; Yang, Z.; Chen, Z.; Zhang, C.Y. (Global and planetary change, 2018)
Changes in riverine suspended and riverbed sediments have environmental, ecological and social implications. Here, we provide a holistic review of water and sediment transport and examine the human impacts on the flux, concentration and size of sediment in the Yangtze River in recent decades. We find that most of the fluvial sediment has been trapped in reservoirs, except for the finest portion. Furthermore, soil-conservation since the 1990s has reduced sediment yield. From 1956-1968 (pre-dam period) to 2013–2015 (post-dams and soil-conservation), the sediment discharge from the sub-basins decreased by 91%; in the main river, the sediment flux decreased by 99% at Xiangjiaba (upper reach), 97% at Yichang (transition between upper and middle reaches), 83% at Hankou (middle reach), and 77% at Datong (tidal limit). Because the water discharge was minimally impacted, the suspended sediment concentration decreased to the same extent as the sediment flux. Active erosion of the riverbed and coarsening of surficial sediments were observed in the middle and lower reaches. Fining of suspended sediments was identified along the river, which was counteracted by downstream erosion. Along the 700-km-long Three Gorges Reservoir, which retained 80% of the sediment from upstream, the riverbed gravel or rock was buried by mud because of sedimentation after impoundment. Along with these temporal variations, the striking spatial patterns of riverine suspended and riverbed sediments that were previously exhibited in this large basin were destroyed or reversed. Therefore, we conclude that the human impacts on sediment in the Yangtze River are strong and systematic. •Sediment flux decreased by 77%–99% in the Yangtze mainstem after dams.•Active riverbed erosion and surficial sediments coarsening were observed.•Human impact on Yangtze River sediment is basin-wide, very strong and systematic.